Desindustrialização da economia brasileira pós 2000: uma análise da dinâmica do emprego industrial no Brasil e no estado de São Paulo - Garrido, Cristiane Santos (2019)
Starting from the concept of deindustrialization, as the advance of the reprimarization and regressive specialization process of the Brazilian economy, which results in the loss of industry participation in Gross Domestic Product and total employment, this dissertation had as main objective to analyze the impacts of the deindustrialization process for the structure of the Brazilian formal market, by sectors of activity, in the post-2000 period. Specifically, it was sought to draw a profile of formal employment in industry in Brazil and the state of São Paulo, to investigate whether deindustrialization confirmed from the loss of formal employment participation in Brazilian industry